The Optimal Selection of Small Portfolios - Blog, B.; van der Hoek, G.; Rinnooy Kan, A. H. G.; Timmer, G. T. (Management Science, 1983)
Portfolios that are risk-return efficient in the sense of Markowitz sometimes contain too many securities to be attractive to the small investor. An optimal portfolio subject to a size constraint can be found by an implicit enumeration algorithm, that is much faster than a previous approach and moreover allows the inclusion of securities whose β-coefficient is negative. A simple and computationally very efficient heuristic method that almost always produces optimal portfolios is described as well.